Transformational Leadership of The School Principle in Building Organizational Culture - Arifin, Fajar; Rofiq, Ainur; Rofiq, Muhammad Husnur (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
This study aims to describe the transformational leadership of the principal in establishing organizational culture at MA NU Hasan Muchyi Kapurejo Pagu Kediri. The purpose of this research was to describe: (1) Transformational leadership of headmaster in improving organizational culture at MA NU Hasan Muchyi Kapurejo Pagu Kediri. (2) The transformational leadership of the principal overcomes the obstacles in establishing organizational culture at MA NU Hasan Muchyi Kapurejo Pagu Kediri. (3) Factors that support and obstruct the transformational leadership of headmaster in developing organization culture at MA NU Hasan Muchyi Kapurejo Pagu Kediri. The method used is qualitative method, with data collection technique: interview, documentation and observation. The step of analyzing data is by collecting data, reducing data, presenting data and then concluding. To examine the validity of the data is carried out tests of credibility, transferability, dependability, and confirmability. The findings ware: (1) Transformational Headmaster Leadership in establishing organizational culture at MA NU Hasan Muchyi Kapurejo Pagu Kediri, Principal could build culture well. The principal organizes certain programs that could build a culture at the MA NU Hasan Muchyi Kapurejo Pagu Kediri. In deciding on programs that can be implemented in the School, the Principal involved all stakeholders in the School. (2) In establishing an organizational culture at MA NU Hasan Muchyi Kapurejo Pagu Kediri, the Principal is a good example for all residents in the School, so that the application of good organizational culture in MA NU Hasan Muchyi Kapurejo Pagu Kediri worked well. (3) As a leader, the Head of Madrasah always provides motivation to all teachers' councils, both orally and in writing and in general or in particular. The principal builds self-awareness on the teacher and communicates well so that the Principal's social relationships could go well